The exploitation of heroic conventions in the OE poem Andreas - Divjak, Alenka (Acta neophilologica, 2012)
This paper examines the function of traditional heroic concepts, typical of the traditional military Germanic society, in the Christian environment of the Old English poem Andreas, whose indebtedness to the traditional heroic poetry has been generally recognised. The paper juxtaposes four examples of traditional heroic ethos from Beowulf, the most detailed example of heroic poetry, and the text to which Andreas is verbally and stylistically very close, with the relevant parallels from Andreas, in order to determine to what extent the traditional images relating to the life of traditional heroic society still retain in Andreas their traditional connotations and to what extent they are imbued with the new Christian meaning.
Keywords: angleška književnost; idiomi; junaška poezija; krščanska tematika; staroangleška književnost